The role of annotated logics in AI: A review paper - Abe, Jair; Nakamatsu, Kazumi; Aharari, Ari; Filho, Joao (Journal of Computer Science and Cybernetics, 2021)
Annotated Logics are a category of non-classical logics that have recently appeared from a historical point of view. They are a type of paraconsistent, paracomplete and non-alethic logic. With the rapid development of AI and Automation and Robotics, more and more theory and techniques were coined to support the various issues that the themes were presenting. This expository work explores how to deal directly with conflicts (contradictions) and paracompleteness directly, without extra-logical devices. Support is given by the paraconsistent annotated evidential logic Et. Some applications are discussed.